Comparative Immunogenicity of Trivalent Influenza Vaccine Administered by Intradermal or Intramuscular Route in Healthy Adults - Belshe, Robert B. (2007)
The present study was undertaken with controls using equal doses ID and IM plus the standard full dose IM to assess the role of route of vaccine in immunogenicity of inactivated influenza vaccine. The study was a prospective, randomized, active-controlled, open label clinical trial conducted in healthy young adult outpatients to compare the effect of route (IM vs ID) on antibody responses to influenza vaccine. Volunteers received 3, 6 or 9 μg of vaccine by ID or IM route; 15 μg IM was also studied. Low doses of vaccine given by either route were almost as immunogenic as the standard 15 μg IM dose of influenza vaccine. ID route was not superior to IM vaccine at inducing antibodies. ID vaccine induced significantly more local inflammatory response than IM vaccine.